Orientational disorder in chiral bilayer dielectric metasurfaces - Tanaka, Katsuya; Rahimzadegan, Aso; Arslan, Dennis; Fasold, Stefan; Steinert, Michael; Falkner, Matthias; Pertsch, Thomas; Decker, Manuel; Rockstuhl, Carsten; Staude, Isabelle (Optics InfoBase Conference Papers, 2021)
Tailored structural disorder in photonic metasurfaces opens new opportunities in advanced light shaping. We study a chiral optical response enabled by rotational disorder in chiral bilayer metasurfaces consisting of low-loss dielectric constituents.
CRIS-Team Scopus Importer:2023-04-20